Early-Age Strength of Ultra-High Performance Concrete in Various Curing Conditions - Jong-Sup Park (Materials, 2015)
The strength of Ultra-High Performance Concrete (UHPC) can be sensitively affected by the curing method used. However, in contrast to the precast plant production of UHPC where a standard high-temperature steam curing is available, an optimum curing condition is rarely realized with cast-in-place UHPC. Therefore, the trend of the compressive strength development of UHPC was experimentally investigated in this study, with a focus on early-age strength by assuming the various curing conditions anticipated on site. Concrete specimens were cured under different conditions with variables including curing temperature, delay time before the initiation of curing, duration of curing, and moisture condition. Several conditions for curing are proposed that are required when the cast-in-place UHPC should gain a specified strength at an early age. It is expected that the practical use of UHPC on construction sites can be expedited through this study.